A compounded second-generation current conveyor using only NMOS transistors - Pienchob, Patra; Kumwachara, Kiattisak; Surakampontorn, Wanlop (My University, 2004)
In this paper, A CMOS compounded Second-Generation Current Conveyor using only N-Channel MOSFET is introduced. The input stage of the presented circuit consists of Differential amplifier circuit and Current follower circuit and the output stage is Cascode current mirror. This structure provides the high impedance at port Y, Z + and Z -, and a low impedance at port X. Futhermore, using Differential amplifier circuit and Current follower circuit as a voltage to current converter the circuit gives low voltage offset. The performance of the proposed circuit is studied through the PSPICE simulations.
Keywords: Cascode current mirror; Current conveyor; Current mode; Differential amplifier